Neurons in Macaque Inferior Temporal Cortex Show No Surprise Response to Deviants in Visual Oddball Sequences - Kaliukhovich, Dzmitry A. (J Neurosci, 2014)
Many studies measured neural responses in oddball paradigms, showing a different response to the same stimulus when presented with a low (deviant) compared with a high probability (standard) in a sequence. Such a differential response is manifested in event-related potential studies as the mismatch negativity (MMN) and has been observed in several sensory modalities, including vision. Other studies showed that stimulus repetition suppresses the neural response. It has been suggested that this adaptation effect underlies the smaller responses to the standard compared with the deviant stimulus in oddball sequences. However, the MMN may also reflect the violation of a prediction based on the sequence of standards, i.e., a surprise response. We examined the presence of a surprise response to deviants in visual oddball sequences in macaque (Macaca mulatta) inferior temporal (IT) cortex, a higher-order cortical area. In agreement with visual MMN studies, single-unit IT responses were greater for the deviant than for the standard stimuli. However, single IT neurons showed no greater response to the deviant stimulus in the oddball sequence than to the same stimulus presented with the same probability in a sequence that consisted of many stimuli. LFPs also showed no evidence of a surprise response. These data suggest that stimulus-specific adaptation, without a surprise-related boost of activity to the deviant, underlies the responses in visual oddball sequences even in higher visual cortex. Furthermore, we show that for IT neurons such adaptive mechanisms take into account a relatively short stimulus history, with weaker effects at longer time scales.